Clinical impact and evolution of mitral regurgitation after TAVI using the new generation self-expandable valves. (15th July 2021) - Giannini, C.; Angelillis, M.; Fiorina, C.; Tamburino, C.; Bedogni, F.; Bruschi, G.; Montorfano, M.; Poli, A.; De Felice, F.; Reimers, B.; Branca, L.; Barbanti, M.; et al.
Abstract: Background: Concomitant mitral regurgitation (MR) impaired prognosis in patients undergoing transcatheter aortic valve implantation (TAVI). It has been suggested that the use of first generation self-expandable valve in patients with significant MR is associated with worse outcome as compared with balloon expandable valve. However, the impact of newer generation transcatheter devices on MR has not been investigated so far. We aim to assess the prognostic impact of MR in patients undergoing TAVI with the first-generation vs. the latest generation of self-expandable valves. Methods: We analyzed 2964 consecutive patients who underwent TAVI. Patients were classified into 4 groups according to the degree of baseline MR and the generation of self expandable valve implanted. Results: Of 1234 patients with moderate or severe MR, 817 were treated with first generation and 417 patients with second generation valves. Whereas, of 1730 patients with no or mild MR, 1130 were treated with first generation and 600 patients with second generation valves. Although, concomitant moderate-severe MR was found to be an independent predictor of mortality after TAVI, the use of newer generation self expandable valves was associated with higher survival rate at 1 year irrespective of the degree of preprocedural MR. At multivariable analysis the use of newer generation valve was associated with MR improvement throughout 1 year follow-up. Conclusion: Baseline moderate-severe MR is associated with an increase in mortality after TAVI. However, the degree of preprocedural MR doesn't impact survival when a second generation self expandable valve is used. Highlights: Moderate-severe preoperative MR is an independent predictors of mortality after TAVI. Significant preoperative MR is associated with worse outcome in particular among patients treated with first generation self-expandable valves. Whit the second generation device the degree of MR at baseline did not affect mortality at 1 years even with the use of self expandable valves.